2016
DOI: 10.1111/1471-0528.14004
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of first‐trimester combined screening for fetal trisomy 21 in a resource‐limited setting in mainland China

Abstract: Objective To assess the feasibility and performance of the firsttrimester combined screening test for trisomy 21 in a resourcelimited setting in mainland China.Design Prospective observational cohort study.Setting First Affiliated Hospital of Kunming Medical University, China.Population Ten thousand four hundred and forty-two pregnant women requesting first-trimester screening.Methods The combined screening test was performed from May 2012 to December 2014. Women with a high-risk result (≥1:600) were offered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…The actual total risk of the fetus being affected by one of the autosomal and sex chromosome aneuploidies, four microdeletion syndromes and 50 single gene diseases is 1 in 65 (Additional file 3). Based on the above estimates, all pregnancies matching the characteristics of our cohort [28,29], a first tier NIPT such as the one presented herein should be integrated as part of standard health care. Accordingly, being aware of the fetal risk, couples can take informed decisions regarding the clinical management of their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The actual total risk of the fetus being affected by one of the autosomal and sex chromosome aneuploidies, four microdeletion syndromes and 50 single gene diseases is 1 in 65 (Additional file 3). Based on the above estimates, all pregnancies matching the characteristics of our cohort [28,29], a first tier NIPT such as the one presented herein should be integrated as part of standard health care. Accordingly, being aware of the fetal risk, couples can take informed decisions regarding the clinical management of their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the cost-effectiveness of the FMF 'screen-and-treat' strategy concluded that routine aspirin administration is the optimal cost-effective approach, compared both with no aspirin administration for prevention and with aspirin administration based on serum biomarker and ultrasound measurements or clinical risk factors 45,46 . However, these studies did not take into account that PE screening can be incorporated alongside first-trimester trisomy screening, which has been validated as cost-effective in both developed and developing countries, including China 47,48 . The relatively low positive predictive value of the preterm PE screening test (e.g.…”
Section: Implications For Clinical Applicationmentioning
confidence: 99%
“…Human chorionic gonadotropin (hCG) is routinely used for first trimester Down's syndrome screening programs worldwide (11,12). hCG could be a determinant of GDM risk as it has been shown to stimulate placental glycogenolysis through activation of adenylate cyclase and its immunomodulatory effects could ameliorate pancreatic autoimmunity (13,14).…”
Section: Introductionmentioning
confidence: 99%